Western Supremacy - Maliha Chishti (International Institute of Islamic Thought, 2004)
This book traces the journey of western domination from the conquest of the Americas to the current forms and practices of globalization and development. Bessis contends that the West, unlike other empires of the past, is the only one to have produced a theoretical (philosophical, moral, and scientific) apparatus to legitimate its supremacy and hegemony around the world. While making her case, she explores what she terms as the ultimate paradox of the West: its ability to produce and even violently promote universals (e.g., democracy, justice, and human rights) and yet, at the same time, exert an inexhaustible capacity to self-justify its own violations of these very universals. It is precisely this capacity to disassociate what it says from what it does, the author asserts, that makes the West both unintelligent and illegitimate to the world. This book, divided into three parts with 12 chapters, provides the reader with an excellent introductory overview of the nature and extent of western domination, as well as the relationship it has fostered with the rest of the world. Part 1, “The Formation of a Culture,” sets out the West’s historicopolitical formation, tracing its birth to the turn of the sixteenth century ...